2017
DOI: 10.1021/acs.jpcb.7b06053
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Steering in Protein Association Revisited: Surprisingly Minuscule Effects of Considerable Torques

Abstract: We investigate the previously postulated hydrodynamic steering phenomenon, resulting from complication of molecular shapes, its magnitude and possible relevance for protein-ligand and protein-protein diffusional encounters, and the kinetics of diffusion-controlled association. We consider effects of hydrodynamic interactions in a prototypical model system consisting of a cleft enzyme and an elongated substrate, and real protein-protein complexes, that of barnase and barstar, and human growth hormone and its bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…It might be surprising that we observe in our Brownian dynamics simulations clear effect of orientational steering by hydrodynamic interactions, whereas such effects were not visible in another Brownian dynamics simulations for the similar receptor–ligand model. 32 Besides the differences in the sophistication of the employed models for hydrodynamic effects calculations, our being much more simplified, the simulation described in that work consisted of one-dimensional translation motion and one-dimensional rotation motion of the ligand with respect to the receptor model, whereas here the ligand has full translational and rotational freedom. The other difference is that our receptor model consists of two arrays built from five beads each, whereas in the other work the receptor model consisted of only two spherical elements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It might be surprising that we observe in our Brownian dynamics simulations clear effect of orientational steering by hydrodynamic interactions, whereas such effects were not visible in another Brownian dynamics simulations for the similar receptor–ligand model. 32 Besides the differences in the sophistication of the employed models for hydrodynamic effects calculations, our being much more simplified, the simulation described in that work consisted of one-dimensional translation motion and one-dimensional rotation motion of the ligand with respect to the receptor model, whereas here the ligand has full translational and rotational freedom. The other difference is that our receptor model consists of two arrays built from five beads each, whereas in the other work the receptor model consisted of only two spherical elements.…”
Section: Resultsmentioning
confidence: 99%
“…Our simple models are expected to maximize orienting hydrodynamic interactions between the receptor and the ligand approaching its binding site. 27 , 32 Moreover, we expect that the electrostatic and hydrodynamic orienting interactions both promote orientation of the ligand shown in Figure 2 on the left. For the electrostatically changed model of the receptor, shown on the right, only hydrodynamic orienting interactions force the approaching ligand to keep parallel orientation with respect to the binding cleft.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to other studies, the results show that while HI predictably change the local properties of a system, it is generally hard to predict the effect of HI on averaged global observables a priori. Antosiewicz et al 83 analyzed the kinetics of diffusional encounters of, among others, Barnase and Barstar, and found that, even though the magnitudes of the torques resulting from the hydrodynamic coupling of the associating molecules were comparable with the magnitudes of the torques from electrostatic interactions, the overall effects of the hydrodynamic torques on the association kinetics were rather small. For studies of solutes in the presence of a surface, there is agreement that the diffusivity of the solutes is re-duced, although there is a strong dependence on the properties and assumptions of the individual systems studied as regards whether this reduction also influences the adsorption properties.…”
Section: Discussionmentioning
confidence: 99%
“…At short distances, however, also the lubrication and many-body forces must be taken into account [8]. To avoid this complication, a macromolecule can be approximated by small spheres placed on its surface [22][23][24][25]; then the RPY tensor between these small spheres is valid in a wide range of macromolecular separations, but the tensor size increases proportionally to the number of spheres taken to approximate the macromolecules.…”
Section: Hydrodynamic Interactionsmentioning
confidence: 99%